Clinical use of antimicrobial regional limb perfusion in adult horses diagnosed with synovial sepsis or penetrating synovial wounds at a single equine referral hospital in the Midwest United States—163 cases (2010–2020) - Loppnow, Zach; Kersh, Kevin; Wang, Chong; Spaethe, Sienna; Troy, Jarrod (Frontiers in Veterinary Science, 2025)
The clinical outcomes in horses diagnosed with established synovial sepsis (SS) or minimally contaminated synovial wounds (SW)/non-established sepsis, following intravenous regional limb perfusion (IVRLP) treatment, have not been reported since 2010. Additionally, previous reports on this subject were confined to just two clinical retrospective reports. This study aimed to provide an update on the short-term (hospital discharge) and long-term (≥1 year) survival rates in adult horses diagnosed with SS or SW treated with IVRLP at a single institution in the USA from 2010–2020. The study also seeks to determine IVRLP variables associated with survival. The medical records of 163 adult equine, either diagnosed with SS (group 1) or SW (group 2), from 2010–2020 treated with IVRLP were reviewed. The short-term survival rate was 88.9% (56 out of 63) for group 1 and 99.0% (99 out of 100) for group 2. The long-term survival rate was 65.1% (41 out of 63) for group 1 and 83.6% (46 out of 55) for group 2. Gentamicin was the most commonly chosen IVRLP antimicrobial choice (153 out of 163 cases). Horses in group 1 were less likely to survive until hospital discharge (p = 0.01; odds ratio [OR] = 0.08; 95% confidence interval [CI]: [0.01, 0.68]). The total number of IVRLPs performed during hospitalization was significantly associated with non-survival to hospital discharge (p = 0.01; OR = 0.47; 95% CI: [0.22, 0.87]), indicating that horses were less likely to survive as the total number of IVRLPs increased. No variables were associated with long-term survival. Overall survival in adult horses diagnosed with SS or SW after treatment is good, and this study provides an updated clinical report on adult equine SS or SW cases that received IVRLP in the USA. This study also reports IVRLP variables, including the total number of IVRLPs and the number of consecutive IVRLPs, that may be associated with short-term survival.